Research Status and Development Prospect of 3D Printing Concrete Materials. Issue 3 (May 2019) - Liu, Gaojie; Bai, Erlei; Xu, Jinyu; Wang, Tengjiao; Chang, Sen
Abstract: With the rapid development of computer-based 3D printing technology, the technology is widely used in all walks of life.[1] Based on the introduction of 3D printing technology, this paper introduces the development of 3D printing technology in the construction industry.The performance requirements of 3D printed concrete materials and the commonly used 3D printed building materials are introduced. Finally, the problems still existing in 3D printing construction technology are summarized and the development prospects are put forward.